Pelaksanaan Online Single Submission (OSS) dalam Rangka Percepatan Perizinan Berusaha di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kabupaten Tabanan - I Kadek Agus Dimas Harta Khanna; I Nyoman Putu Budiartha; Ida Ayu Putu Widiati (Jurnal Analogi Hukum, 2024)
Licensing is an important aspect of public services, one of which is business licensing. The innovation of business services provided by the government is Online Single Submission (OSS) which makes it easier for business actors to take care of business licensing. The implementation of this new system has obstacles to implementation, the fact that OSS is not widely known by the public and is not evenly distributed in the local government sector. The method used in this research is empirical juridical. The results showed that the DPMPTSP of Tabanan Regency in carrying out the implementation of business licensing referred to the Job Creation Law and Government Regulation No. 5 of 2021 concerning the Implementation of Risk-Based Business Licensing. Risks are classified into low, low medium, high medium, and high risks. The implementation of accelerated licensing at the DPMPTSP of Tabanan Regency consists of the implementation of registration, legality, data collection, risk analysis, permit issuance, facilities, and supervision. The obstacles that occur in the implementation are divided into two, namely internal aspects and external aspects. Internal aspects are Human Resources (HR) and Infrastructure Facilities and external aspects are OSS website barriers, supporting regulations and supervision.